Chronic wasting disease in Europe: characterisation of genetic susceptibility and strain diversity - Robinson, Amy Louise (The University of Edinburgh, 2022)
Chronic wasting disease (CWD) is a prion disease that causes a fatal, progressive neurodegenerative disorder in cervid species including deer, elk, reindeer and moose. CWD has become widespread in North America in both wild and farmed cervid populations; disease control poses significant challenges due to efficient horizontal transmission and environmental persistence. The recent identification of CWD affecting reindeer, moose and red deer in Norway and other Scandinavian countries threatens a similar pattern of spread in European cervids, impacting the health of wild populations as well as deer farming and hunting industries. It is widely accepted that prion diseases are associated with an unusual infectious agent, a misfolded, protease resistant, self-propagating isoform (PrPSc) of the normal cellular prion protein (PrPC). Susceptibility is largely determined by the sequence of the prion protein gene (PRNP). In North America, PRNP polymorphisms in cervid species have been associated with reduced susceptibility, altered pathogenesis and the emergence of new CWD strains. Understanding CWD in the European context cannot be solely based on North American evidence due to the differences in cervid species and unknown effects of novel strains. I aimed to characterise the PRNP polymorphisms in British deer species and predict their effects on CWD susceptibility using in-vitro assays. I also aimed to determine if the pathological phenotypic characteristics of Norwegian and Canadian CWD isolates are maintained in primary passage to wild-type mice, and if lymphoid replication is an important feature in primary passage. To determine the PRNP variation in British cervid species, a large-scale survey of the six most numerous species of wild deer in the UK was performed, including red (Cervus elaphus), sika (Cervus nippon), roe (Capreolus capreolus), fallow (Dama dama), muntjac (Muntiacus reevesii), and Chinese water deer (Hydropotes inermis), which was compared with two smaller surveys of red deer from Norway and the Czech Republic. The PRNP gene is well conserved in cervid species, and we identified low levels of variation in most cervid species, particularly roe deer, which were identical in all individuals analysed. Based on comparison with susceptible North American deer species, it is likely that a high proportion of the UK deer population would be susceptible at least to the strains of CWD present in North America. Red deer showed the most PRNP variation, with five haplotypes identified which varied in frequency depending on location: the P168S and I247L polymorphisms were only identified in Scottish and Czech populations, respectively. These novel polymorphisms are not present in North American cervid populations, and their impact on CWD susceptibility are unknown. The effects of PRNP variants on CWD susceptibility may be determined in naturally infected cervid populations, experimental challenge of cervids, or in transgenic mice expressing cervid prion proteins. The mechanisms by which individual amino acid substitutions influence disease susceptibility and pathogenesis are likely to include modification of epitopes crucial for PrPC structure, stability, and conversion to PrPSc. These effects may be reproduced using in-vitro assays that analyse the conversion efficiency of different PrP protein sequences by PrPSc derived from prion-infected tissues. To test the misfolding capacity and conversion efficiency of British deer PRNP variants, two in-vitro assays were developed: a recombinant PrP protein fibrillisation assay and a cell-lysate protein misfolding amplification assay (PMCA) using RK13 cells transfected with red deer PRNP sequences as substrate. Analysis of Norwegian CWD isolates and their transmission into rodent models has provided preliminary evidence that there are several different strains present in reindeer and moose which differ from those in North America. The gold standard test for strain differentiation is bioassay and assessment of the differences in heritable phenotypes in a new host species. As part of ongoing strain-typing studies of Norwegian CWD, I describe the primary passage of isolates from the first Norwegian reindeer and moose cases, as well as two Canadian CWD isolates, in well-defined panels of wild-type mice (VM, C57BL/6J and RIII) which have been used extensively in previous strain-typing experiments. Evidence of transmission was examined in both brain and lymphoid tissues using a combination of immunohistochemistry, western blot and RT-QuIC amplification. Low transmission rates were observed for the transmission of natural CWD cases from Norway and Canada, however transmission rates were high for an experimental H95+ strain isolate with 72% of mice showing evidence of infection, 40% of which exhibited clinical signs. The work presented here represents some of the first steps towards understanding PRNP variation in European cervid populations, developing methods for the assessment of novel PRNP polymorphisms, and the characterisation of European strain diversity. It is unclear if the efforts made to contain CWD in Norway will be successful, and further research is urgently required to inform risk assessments and control strategies. The origins of CWD remain unknown, and it is possible that further novel instances of CWD will be identified in different cervid species and geographic locations. The emergence of CWD in Europe poses a considerable challenge, the extent of which will critically depend on the susceptibility of cervid populations and the characterisation of new prion strains that may differ in their ability to transmit to other species including livestock and man.
Keywords: chronic wasting disease; CWD; wild deer health; prion diseases; PRNP variation; PrP variants; red deer; susceptibility of deer populations